PENGARUH KEIKUTSERTAAN DALAM KEGIATAN EKSTRAKURIKULER TERHADAP PRESTASI BELAJAR MELALUI KEDISIPLINAN BELAJAR SISWA SEKOLAH MENENGAH ATAS - Andri Eko Prabowo; Yustri Yuhelma (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study explores the impact of student participation in extracurricular activities on learning achievement mediated by learning discipline. This research was conducted at SMA Negeri 1 Seberida, Indragiri Hulu Regency, with a sample of 30 students in class XI IPS. This research uses a quantitative approach with descriptive quantitative research type, the data analysis used to test the hypothesis is path analysis. The results showed that extracurricular activities have a positive but insignificant direct and indirect effect on learning achievement mediated by student discipline. The results of this study confirm previous research which states that there is a positive and significant effect of participation in extracurricular activities on discipline and learning achievement. However, this study was able to show that discipline and learning achievement can be controlled by school management policies in maintaining student discipline and achievement.